Cord blood vitamin D and the risk of acute lower respiratory infection in Indigenous infants in the Northern Territory. Issue 6 (4th April 2016) - Binks, Michael J; Smith‐Vaughan, Heidi C; Marsh, Robyn; Chang, Anne B; Andrews, Ross M
Abstract: Objectives: To assess vitamin D status in Indigenous mothers and infants in the Northern Territory, and to determine whether cord blood vitamin D levels are correlated with the risk of infant hospitalisation for acute lower respiratory infection (ALRI). Design and participants: Within a nested cohort of 109 Indigenous mother–infant pairs recruited between 2006 and 2011, we used liquid chromatography–mass spectrometry to measure vitamin D (25(OH)D3 ) levels in maternal blood during pregnancy ( n = 33; median gestation, 32 weeks [range, 28–36 weeks]) and at birth ( n = 106; median gestation, 39 weeks [range, 34–41 weeks]), in cord blood ( n = 84; median gestation, 39 weeks [range, 36–41 weeks]), and in infant blood at age 7 months ( n = 37; median age, 7.1 months [range, 6.6–8.1 months]). Main outcome measure: ALRI hospitalisations during the first 12 months of infancy, identified using International Classification of Diseases coding (J09–J22, A37–A37.9). Results: Compared with mean 25(OH)D3 levels in maternal blood during pregnancy (104 nmol/L), mean levels were 23% lower in maternal blood at birth (80 nmol/L) and 48% lower in cord blood samples (54 nmol/L). The mean cord blood 25(OH)D3 concentration in seven infants subsequently hospitalised for an ALRI was 37 nmol/L (95% CI, 25–48 nmol/L), lower than the 56 nmol/L (95% CI, 51–61 nmol/L) in the 77 infants who were not hospitalised with an ALRI ( P = 0.025). Conclusions: Cord blood 25(OH)D3 concentrations were about half those in maternal blood during the third trimester of pregnancy (about 7 weeks earlier). Most cord blood levels (80%) were classified as vitamin D insufficient (< 75 nmol/L) by existing guidelines, and were lower among infants who were subsequently hospitalised with an ALRI.